Calcium Signaling in Human Health and Diseases - Francesco Moccia (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Intracellular Ca2+ signaling is witnessing an amazing resurgence of interest. In addition to traditional Ca2+ aficionados, an astonishing (and growing) number of colleagues from all around the world have started to devote a large part of their research to gain insights into the role of Ca2+ signaling in health and disease. This is why calcium ions interact with virtually every signal transduction pathway not only in mammalian cells, but also across the phylogenetic tree, thereby, driving or modulating most, if not all, cellular functions, ranging from fertilization to apoptosis, passing through learning and memory, cardiac contractility, and immune response. This book gathers a collection of original research articles and reviews by a number of renowned experts who aim to present the state of the art of many pathophysiological aspects of intracellular Ca2+ signaling, such as embryonic development, immune response, extracellular Ca2+ signaling, neoplastic transformation, muscle hypertrophy, pulmonary inflammation, and P2X receptor gating.